Does Germany Need a (New) Research Ethics for the Social Sciences? - Claudia Oellers; Eva Wegner (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
This paper evaluates the German, UK, and US approaches to dealing with research ethics in the social sciences. It focuses 1) on the extent to which these research ethic frameworks protect the key rights of research subjects and 2) the extent to to which they take into account the methodology and approaches used in social science and do not simply emulate those of the natural sciences. The U.S. approach stands for a highly regulated, and partly bureaucratic, approach where the ethics review is modeled on the methodology of natural sciences. In the UK, in contrast, a social science research ethics framework has been developed that remedies some of these shortcomings. It is implemented through pressure from funding institutions and aims to respond to the needs of social science research. The German social science ethics framework consists of non-binding codes of conduct, guidelines about good scientific practice, and ethic codes of the German professional associations and funding institutions. We find that ethical behavior in Germany is most typically understood as ethical behavior towards the peers. We recommend the establishment of a new research ethics framework for the social sciences in Germany modeled on the UK's.
Keywords: 330; research ethics; good scientific practice; institutional review boards